Direct transfer to angiosuite for patients with severe acute stroke treated with thrombectomy: the multicentre randomised controlled DIRECT ANGIO trial protocol. Issue 3 (15th March 2021) - Riou-Comte, Nolwenn; Zhu, François; Cherifi, Aboubaker; Richard, Sébastien; Nace, Lionel; Audibert, Gérard; Achit, Hamza; Costalat, Vincent; Arquizan, Caroline; Beaufils, Olivier; Consoli, Arturo; Lapergue, Bertrand; et al.
Abstract : Introduction: Mechanical thrombectomy (MT) increases functional independence in patients with acute ischaemic stroke with anterior circulation large vessel occlusion (LVO), and the probability to achieve functional independence decreases by 20% for each 1-hour delay to reperfusion. Therefore, we aim to investigate whether direct angiosuite transfer (DAT) is superior to standard imaging/emergency department-based management in achieving 90-day functional independence in patients presenting with an acute severe neurological deficit likely due to LVO and requiring emergent treatment with MT. Methods and analysis: DIRECT ANGIO (Effect of DIRECT transfer to ANGIOsuite on functional outcome in patient with severe acute stroke treated with thrombectomy: the randomised DIRECT ANGIO Trial) trial is an investigator-initiated, multicentre, prospective, randomised, open-label, blinded endpoint (PROBE) study. Eligibility requires a patient ≤75 years, pre-stroke modified Rankin Scale (mRS) 0–2, presenting an acute severe neurological deficit and admitted within 5 hours of symptoms onset in an endovascular-capable centre. A total of 208 patients are randomly allocated in a 1:1 ratio to DAT or standard management. The primary outcome is the rate of patients achieving a functional independence, assessed as mRS 0–2 at 90 days. Secondary endpoints include patients presenting confirmed LVO, patients eligible to intravenous thrombolysis alone, patients with intracerebral haemorrhage and stroke-mimics, intrahospital time metrics, early neurological improvement (reduction in National Institutes of Health Stroke Scale by ≥8 points or reaching 0–1 at 24 hours) and mRS overall distribution at 90 days and 12 months. Safety outcomes are death and intracerebral haemorrhage transformation. Medico-economics analyses include health-related quality of life and cost utility assessment. Ethics and dissemination: The DIRECT ANGIO trial was approved by the ethics committee of Ile de France 1. Study began in April 2020. Results will be published in an international peer-reviewed medical journal. Trial registration number: NCT03969511 .